Hostile Takeover Law and the Challenges in Market for Corporate Control: A Comparative Analysis between Indonesia and the United Kingdom - Salim, Yeselia; Prisandani, Ulya Yasmine (Universitas Negeri Gorontalo, 2022)
The concept of hostile takeover is still unrecognized under Indonesian laws and regulations despite its importance in keeping the corporate board in check and corporate governance better implemented in a company. This article seeks to explore the extent of the current environment and regulation in Indonesia able in accommodating hostile takeover in relation to the market for corporate control in Indonesia by using hostile takeover as a mechanism to measure. A comparative analysis is then conducted with the United Kingdom United Kingdom as a country with an active market for corporate control, specifically with the methods employed to deal with hostile takeover.